CNS-Directed Cancer Treatment and Child Adjustment: Moderating Effects of Maternal Parenting. (18th March 2022) - Winning, Adrien M; Howard Sharp, Katianne; Ferrante, Amanda C; Ralph, Jessica; Desjardins, Leandra; Friedman, Debra L; Young-Saleme, Tammi K; Vannatta, Kathryn; Compas, Bruce E; Gerhardt, Cynthia A
Abstract: Objective: The aim of this study was to examine whether maternal parenting behaviors (i.e., warmth, behavioral/psychological control) moderate the association between central nervous system (CNS)-directed treatment and adjustment among pediatric cancer survivors at 3 years post-diagnosis or relapse. Methods: Three years after their child's cancer diagnosis or relapse, mothers ( N  =   84) reported on their child's academic and social competence, as well as their internalizing and externalizing problems. Children ( N  =   84; M age = 13.21 years, 52.4% male) reported on maternal parenting behaviors. Using medical chart data, children were separated into CNS (i.e., received cranial radiation, intrathecal chemotherapy, and/or neurosurgery; N  =   45) or non-CNS-directed treatment ( N  =   39) groups. Twelve moderation models were tested when examining two-way interactions between CNS treatment group and maternal parenting behaviors. Results: Children in the CNS-directed treatment group demonstrated significantly worse academic and social competence. Moderation analyses revealed four significant two-way interactions between CNS treatment group and maternal parenting behaviors when predicting children's adjustment. High levels of maternal behavioral control buffered the negative impact of CNS-directed treatment on children's social competence. In addition, maternal warmth had a contrasting effect, as CNS-directed treatment was associated with worse academic competence at high levels of warmth. Analyses with psychological control revealed that low levels of this parenting style were not protective against internalizing or externalizing problems among those with CNS-directed treatment. Conclusions: Children who receive CNS-directed treatment may benefit from a different pattern of parenting during early cancer survivorship. Findings highlight the importance of considering the broader family context when conceptualizing the impact of illness-related factors on adjustment among pediatric cancer survivors.